Determinants of Liver Complications Among HIV/Hepatitis B Virus–Coinfected Patients. (1st September 2019) - Lo Re, Vincent; Newcomb, Craig W.; Carbonari, Dena M.; Roy, Jason A.; Althoff, Keri N.; Kitahata, Mari M.; Reddy, K. Rajender; Lim, Joseph K.; Silverberg, Michael J.; Mayor, Angel M.; Horberg, Michael A.; Cachay, Edward R.; et al.
Abstract : Background: Hepatitis B virus (HBV) infection is a leading cause of end-stage liver disease (ESLD) and hepatocellular carcinoma (HCC) in HIV. Factors contributing to the high rates of liver complications among HIV/HBV-coinfected individuals remain unknown. Setting: North American AIDS Cohort Collaboration on Research and Design. Methods: We performed a retrospective cohort study among HIV/HBV-coinfected patients in 10 US and Canadian cohorts of the North American AIDS Cohort Collaboration on Research and Design that validated ESLD (ascites, spontaneous bacterial peritonitis, variceal hemorrhage, and/or hepatic encephalopathy) and HCC diagnoses from 1996 to 2010. Multivariable Cox regression was used to examine adjusted hazard ratios [aHRs with 95% confidence interval (CIs)] of liver complications (first occurrence of ESLD or HCC) associated with hypothesized determinants and with increasing durations of HIV suppression (⩽500 copies/mL). Results: Among 3573 HIV/HBV patients with 13, 790 person-years of follow-up, 111 liver complications occurred (incidence rate = 8.0 [95% CI: 6.6 to 9.7] events/1000 person-years). Rates of liver complication were increased with non-black/non-Hispanic race [aHR = 1.76 (1.13–2.74)], diabetes mellitus [aHR = 2.07 (1.20–3.57)], lower time-updated CD4 cell count [<200 cells/mm 3 : aHR = 2.59 (1.36–4.91); 201–499 cells/mm 3 : aHR = 1.75 (1.01–3.06) versus ≥500 cells/mm 3 ], heavy alcohol use [aHR = 1.58 (1.04–2.39)], and higher FIB-4 at start of follow-up [>3.25: aHR = 9.79 (5.73–16.74); 1.45–3.25: aHR = 3.20 (1.87–5.47) versus FIB-4 <1.45]. HIV suppression for ≥6 months was associated with lower liver complication rates compared with those with unsuppressed HIV [aHR = 0.56 (0.35–0.91)]. Conclusions: Non-black/non-Hispanic race, diabetes, lower CD4 cell count, heavy alcohol use, and advanced liver fibrosis were determinants of liver complications among HIV/HBV patients. Sustained HIV suppression should be a focus for HIV/HBV-coinfected patients to reduce the risks of ESLD/HCC. Abstract : Supplemental Digital Content is Available in the Text.